Emergy-based evaluation of production efficiency and sustainability of diversified multi-cropping systems in the Yangtze River Basin - Lei, Xinhui; Liang, Bing; Feng, Liang; Zhao, Xuyang; Pu, Tian; Yu, Changbing; Wang, Shubin; Wei, Yafeng; Ma, Shumei; Wang, Xiaochun; Yang, Wenyu (Frontiers in Plant Science, 2024)
soybean (upper reaches of the YRB), forage rape-corn/soybean or potato/corn/soybean (middle reaches of the YRB), and wheat-corn/soybean (lower reaches of the YRB) to facilitate the coexistence of high economic benefits and environmental sustainability.Additionally, promoting mechanization and reducing labor input was essential to improve the efficiency and sustainability of multi-cropping systems. This study would provide a scientific basis and theoretical support for the development of efficient and sustainable multiple-cropping systems in the dryland of the YRB.